What Do Child Protection Social Workers Talk about When They Talk about Helping Children and Families? An Observational Study of Supervision. Issue 2 (15th March 2023) - Wilkins, David; Pitt, Charlotte; Addis, Samia
Abstract : Social work is often described as a helping profession. Yet in the context of child protection services, the kind of 'help' on offer is not always welcome. Relatively few parents or children request the assistance of child protection services, and child protection investigations are often highly stressful. Workers and family members may have different ideas about the nature of the family's problems, and the type of support they need. So, how do child protection social workers think they are helping children and their families? In this paper, we report an analysis of audio-recordings of supervision case discussions, through which we explore what social workers talk about when they talk about helping families. In some cases, workers did not know how they were helping, or even if they were. Other times, workers said they were helping by developing positive relationships, addressing parental behaviour change, coordinating with other services, and fulfilling their statutory duties. We reflect on these findings in relation to the nature of 'help' in child protection services, practice epistemologies and Hasenfeld's typologies of power.